“The High Mass of Democracy” —Why Germany Remains Aloof to the Idea of Electronic Voting - Fitzpatrick, Jasmin; Jöst, Paula (Frontiers in Political Science, 2022)
Despite the increase in citizens' use of absentee voting and examples from other countries, so far Germany remains aloof to the idea of introducing electronic voting as another form of convenience voting to its political elections. Apart from intra-party elections, no changes in the direction of electronic voting are considered in the current debate about an electoral reform. What are the reasons for the German aloofness toward electronic voting? In this article, we focus on party positions and institutional, as well as legal considerations, to provide a comprehensive answer to this question. From a normative point of view, the question of electronic voting is inextricably linked to the concept of electoral integrity, as the latter is pivotal to determine a democratic mode to select trusted representatives. Therefore, this paper first discusses the opportunities and risks for electoral integrity associated with electronic voting. Based on these considerations, we then explore reasons for the hesitancy of German legislators. To this end, we conducted expert interviews with German MPs and considered open-source documents related to the German debate about electronic voting. Our paper contributes to research on party positions on electronic voting, by relating the topic to questions about electoral integrity and considering political parties' reasoning, as well as legal and institutional constraints in the German context. We find that the main reasons provided by party representatives circle around concerns about transparency, security, accuracy, and the value of the voting act itself.